Evaluation protocol of sound localization - Peixoto, Maria Conceição (2019)
Objective: To explore evaluation tests of the sound localization and to appreciate their use in daily clinical practice. Study Design: prospective study. Material and methods: The authors propose a protocol for the evaluation of sound localization for patients proposed to auditory implantation, in order to evaluate the integration of binaural information. Seven loudspeakers were used, arranged in a radius of 180°, separated by an angle of 30° between them. A 1000Hz warble tone was randomly presented at 60dB SPL from the loudspeakers. Results: The result obtained is the mean error and the overall error. Three clinical conditions were evaluated. Conclusion: Although still in an experimental phase and with possibility of adjustments, it is considered that this evaluation, together with the study of speech discrimination in noise, will allow to understand the integration of hearing information in patients with auditory implants and to evaluate its real binaural integration.